2017
DOI: 10.1002/sctm.16-0382
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Causes Apoptosis of Adult Hippocampal Neural Stem Cells and Memory Impairment Through the Action on AMPK-PGC1α Signaling in Heart Failure

Abstract: Data are limited on the mechanisms underlying memory impairment in heart failure (HF). We hypothesized that angiotensin II (Ang II) may determine the fate of adult hippocampal neural stem cells (HCNs), a cause of memory impairment in HF. HCNs with neurogenesis potential were isolated and cultured from adult rat hippocampi. Ang II decreased HCN proliferation in dose‐ and time‐dependent manners. Moreover, Ang II treatment (1 µM) for 48 hours induced apoptotic death, which was attenuated by pretreatment with Ang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…We observed that both AT1 and AT2 receptors were involved in regulation of proliferation of V-SVZ cells ( Figure 8A), and that the expression of AT1 and AT2 receptors (i.e., AT1/AT2 ratio) may be modified by aging, drugs such as AT1 receptor antagonists (candesartan), or species differences ( Figure 8B). The results are consistent with previous studies showing immunoreactivity for AT1 and AT2 receptors in aggregates of precursor cells obtained from developing brain tissue [19], and with a timedependent increase in AT1 and AT2 receptor expression in cultured rat NSCs derived from embryonic and adult hippocampus [68,69]. Using confocal microscopy, we observed that AT1 and AT2 receptors were mostly expressed in V-SVZ neuroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that both AT1 and AT2 receptors were involved in regulation of proliferation of V-SVZ cells ( Figure 8A), and that the expression of AT1 and AT2 receptors (i.e., AT1/AT2 ratio) may be modified by aging, drugs such as AT1 receptor antagonists (candesartan), or species differences ( Figure 8B). The results are consistent with previous studies showing immunoreactivity for AT1 and AT2 receptors in aggregates of precursor cells obtained from developing brain tissue [19], and with a timedependent increase in AT1 and AT2 receptor expression in cultured rat NSCs derived from embryonic and adult hippocampus [68,69]. Using confocal microscopy, we observed that AT1 and AT2 receptors were mostly expressed in V-SVZ neuroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…However, in an in vitro examination, AT1R activation elicited by chronic (over 24 h) and high dose (over 10 À7 M) application of Ang II was found to directly induce apoptosis of cultured hippocampal neural stem cells isolated from rats (Kim et al, 2017). Also, it has been shown that heart failure elicits AT1Rmediated cell death of newborn hippocampal neurons in rats (Kim et al, 2017). In the present study, however, we did not observe a decrease in neuronal progenitors or newborn neurons.…”
Section: Discussioncontrasting
confidence: 79%
“…Taken together, these results indicate that the increased level of CORT may be transient when evoked during short-term heat exposure, with regulation not dependent on AT1R. However, in an in vitro examination, AT1R activation elicited by chronic (over 24 h) and high dose (over 10 À7 M) application of Ang II was found to directly induce apoptosis of cultured hippocampal neural stem cells isolated from rats (Kim et al, 2017). Also, it has been shown that heart failure elicits AT1Rmediated cell death of newborn hippocampal neurons in rats (Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
“…A recent study has proved that the effects of METH-induced neuroinflammation and neurotoxicity are attenuated through inhibition of NF-κB/STAT3/ERK and mitochondria-mediated apoptosis pathway in dopaminergic SH-SY5Y cells [65]. A previous study showed that Ang II induces apoptotic death, which is attenuated by pretreatment with Ang II receptor blockers in hippocampal neural stem cells [66]. Evidence has indicated that METH-induced apoptotic death in SH-SY5Y cell line is mediated, at least in part, through an ERdependent mechanism [67].…”
Section: Discussionmentioning
confidence: 99%